2006
DOI: 10.1107/s1600536806002315
|View full text |Cite
|
Sign up to set email alerts
|

Bis(1,10-phenanthroline-κ2N,N′)(sulfato-κ2O,O′)cobalt(II) 1,2-ethanediol solvate

Abstract: In the title compound, [Co(SO4)(C12H8N2)2]·C2H6O2, a twofold rotation axis passes through the Co and S atoms, and through the mid‐point of the solvent C—C bond. The coordination environment of the CoII centre is a distorted CoN4O2 octa­hedron, with four N atoms from two chelating 1,10‐phenanthroline ligands and two O atoms from a bidentate sulfate ligand. The two chelating N2C2 groups are oriented at 70.16 (6)° to each other. Inter­molecular O—H⋯O hydrogen bonds help to stabilize the structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…In the crystal structures (1) and (2), one of the squarates adopts a bridging position between the metal atoms, coordinating via two of its O atoms in a l-1,3 fashion, forming a dimeric metal unit, while the other squarate acts as a counter anion. The bite angles of the phen ligands are not significantly different [78.11 (7) and 77.27(6)°for the N1/N2 and N3/N4 in (1), 74.04(6) and 73.34(5)°for the N1/N2 and N3/N4 in (2), respectively] and they are in agreement with those previously reported for phen containing cobalt(II) and manganese(II) complexes [37,38].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the crystal structures (1) and (2), one of the squarates adopts a bridging position between the metal atoms, coordinating via two of its O atoms in a l-1,3 fashion, forming a dimeric metal unit, while the other squarate acts as a counter anion. The bite angles of the phen ligands are not significantly different [78.11 (7) and 77.27(6)°for the N1/N2 and N3/N4 in (1), 74.04(6) and 73.34(5)°for the N1/N2 and N3/N4 in (2), respectively] and they are in agreement with those previously reported for phen containing cobalt(II) and manganese(II) complexes [37,38].…”
Section: Resultssupporting
confidence: 92%
“…Each phen group is planar and bond distances and angles within the limits of error are as expected [37,38]. The dihedral angles between the l-squarate plane and the phen mean planes are 87.90(5) and 70.79(4)°for (1) and 89.23 (5) and 75.65(4)°for (2), while those between the phen mean planes are 85.82(4)°for (1) and 86.61(4)°for (2).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of zinc-phenanthroline complexes with monodentate (Harvey et al, 2000;2003) and bidentate bridging (Harvey et al, 2000) sulfate have been reported. The title zinc complex, (I), is isostructural with the recently reported cobalt(II) and cadmium(II) (Zhong et al, 2006;Lu et al, 2006) analogues.…”
Section: Commentmentioning
confidence: 70%
“…During attempts to synthesize mixed-ligand coordination polymers of transition metals with phen as second ligand via solvothermal reactions, we obtained compounds with a structure composed of a bidentate-chelating sulfate ligand, e.g. (Zhong et al, 2006) (C 10 H 8 N 2 ) 2 ] complex and a solvent butane-2,3-diol molecule. Twofold rotation axes pass through the Co and S atoms and the mid-point of the central C-C bond of the butane-2,3-diol solvent molecule.…”
Section: S1 Commentmentioning
confidence: 99%